BUDAYA PANTANG MAKANAN PADA IBU MENYUSUI DI WILAYAH HAMBUKU BARU KEC. BABIRIK KAB. HULU SUNGAI UTARA - Noveni, Anastasia; Maulana, Erdi; Hadianor, Hadianor; Hasanuddin, Hasanuddin; Saputra, M Yudi; Ilmi, Bahrul (Midwifery And Complementary Care, 2025)
Background: Myths or hereditary beliefs about food taboos for breastfeeding mothers are still widely found in society. In the Banjar Tribe, there are also food taboos for breastfeeding mothers, namely not being allowed to eat snakehead fish and karawila vegetables (oyong), so that it can reduce the mother's nutritional intake which will affect the mother's health and milk production. Objective:. Food restrictions for breastfeeding mothers are not allowed to eat toman fish and karawila vegetables (oyong). This study aims to understand the practice of food restrictions among breastfeeding mothers in Hambuku Baru Village, Babirik District, North Hulu Sungai Regency. Methods: The method used is qualitative research, data collection through in-depth interviews and observations with purposive sampling of five breastfeeding mothers who practice the culture of food restrictions. Result: The results showed that the prohibition of toman fish and karawila vegetables (oyong) is based on hereditary traditions aimed at maintaining the health of mother and child. so this practice has a negative impact on the nutritional fulfillment of breastfeeding mothers, breast milk quality, and child's weight development. Cultural factors and access to health services influence mothers' decisions to follow the restrictions Conclusion: This research provides insights on the importance of educating the public regarding nutrition for breastfeeding mothers without ignoring local cultural sensitivities. Keywords: Food Restriction, Breastfeeding Mothers, Cultural Traditions.